URGENSI PEMBELAJARAN HUMANIS DI SEKOLAH - Dudiyono (CV. Amerta Media, 2017)
When we observe the learning process that occurs during this time, as if the meaning of learning in school has undergone a shift in orientation, learning in context, there is now a tendency to only obtain the values in terms of